Biochar stability and impact on soil organic carbon mineralization depend on biochar processing, aging and soil clay content. (June 2022) - Yang, Yan; Sun, Ke; Han, Lanfang; Chen, Yalan; Liu, Jie; Xing, Baoshan
Abstract: The carbon sequestration potential of biochar depends on its stability in the soil and its priming effect on native soil organic carbon mineralization, which could be expected to be in turn affected by biochar processing, aging and soil clay content. This study applied stable carbon isotopes (δ 13 C) to quantify the mineralization of fresh and aged biochar pyrolyzed at 300, 450, and 600 °C and their priming effects on native soil organic carbon in two types of soils with different clay contents. At the end of the incubation, the total carbon loss of biochar-amended soil was 16–53% lower than that of unamended soil and the lowest carbon loss was found in soils amended with 600 °C biochar. Regardless of soil type, the proportion of biochar-carbon (carbon in the biochar) mineralized decreased with increasing pyrolysis temperature. For fresh biochar, the proportion of carbon mineralized was 13–47% higher in the sandy loam soil than in the sandy clay loam soil at the end of the incubation. However, soil type had a minimal effect on the mineralization proportion of aged biochar-carbon. The dissolved organic carbon increased after fresh and aged biochar was added to the sandy clay loam, but not the sandy loam, suggesting less carbon hydrolysis and solubilization from native soil organic carbon and biochar in the sandy loam soil. Moreover, biochar amendment increased the enzyme activities in sandy clay loam soil and either increased or had no effect on those in sandy loam soil. Fresh biochar had no effect on native soil organic carbon mineralization after it was applied, although a negative priming effect was observed after two−7 wk. For aged biochar, a negative priming effect was found for both soils. These findings demonstrated that biochar was more stable in clayey soils, and biochar produced at higher temperature indeed showed high soil carbon sequestration potential. Graphical abstract: Image 1 Highlights: Biochar was more stable in sandy clay loam soil than in sandy loam soil. Fresh biochar had no priming effect on soil organic carbon in the early stage. Fresh/aged biochar had a negative priming effect on soil organic carbon. Both fresh and aged biochar addition reduced carbon loss from soil.